High Mortality Among Clinically Pneumocytis Pneumonia Infection in Low CD4 HIV Patients: Case Series - Iin Novita Nurhidayati Mahmuda; Dhani Redhono Harioputro; R. Satriyo Budhi Susilo; Tatar Sumandjar; Arifin Arifin (Biomedika, 2024)
Objective: The number of HIV cases in Indonesia reached a peak in 2019 with 50,282 cases dispersed over 407 of 507 districts and cities (or 80%) of the country's provinces. Central Java is the province after DKI Jakarta and East Java which has a mortality of 12.41 and an HIV/AIDS prevalence of 22% of all cases. High mortality in HIV patients influenced by very low CD4 count ≤ 50 cells/mm3. Identification of clinical characteristics, risk factors and causes of death is very important to carry out optimal management of HIV/AIDS for delaying the progression of infection and saving lives. Design and method: We identified three patients with newly diagnosed HIV between January to April, 2023. We provide demographic data, clinical characteristics, laboratory examination, chest x-ray imaging and final outcome. Results: We presented 3 newly diagnosed HIV patients. They are still young < 40 years old, the majority have BMI < 18.5. Major opportunistic infections are oral candidiasis (100%), Pruritic Popular Eruption (PPE), pulmonary infection due to Tuberculosis, Pneumocystis pneumonia (PCP) and bacterial pneumonia. Hematological alteration dominated by anemia. Increased of transaminase enzyme and hyponatremia are also common. All patients had CD4 count < 20 cells/mm3, only one patient survived. Causes of death were pulmonary infection mainly due to clinical PCP. Conclusion: PCP is one of the fatal opportunistic infections in HIV. It is necessary to be diagnosed as early as possible so that patients can start Anti-Retro Viral (ARV) at an early stage to improve prognosis.